Meningkatkan motivasi belajar siswa korban bullying melalui teknik self-regulation - Rossyka, Maqhfira Maulia (Maliki Interdisciplinary Journal, 2023)
Learning motivation has an important role in increasing student achievement. Students with high learning motivation have a strong desire to complete their assignments as well as possible. Meanwhile, students who have low learning motivation tend not to be enthusiastic in completing assignments so that it affects their achievement at school. There are various factors that influence the decrease in student learning motivation, one of which is bullying. Bullying often occurs in the school environment. The impacts are various, such as anxiety, fear, and even reluctance to go to school. This makes bullying one of the causes of decreased motivation to learn. The self-regulation technique applied can help students increase learning motivation. Self-regulation in students helps students understand themselves, increase self-confidence and be able to control themselves well. The purpose of this study was to see the relevance of bullying to decreased student motivation and the effectiveness of self-regulation techniques to increase student motivation, through the method of literature study. The results of the literature study show that self-regulation techniques can help increase learning motivation in students who are victims of bullying.